2010
DOI: 10.4097/kjae.2010.58.4.334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ulinastatin on cytokine reaction during gastrectomy

Abstract: BackgroundInflammation plays an important role in the postoperative morbidity of organs, which is related to the activation of pro-inflammatory and anti-inflammatory cytokines. Ulinastatin (Urinary trypsin inhibitor, UTI) is a serine protease inhibitor found in human urine or serum that inhibits the activation of human leukocyte elastase. This study examined the effect of UTI on the inflammation response in patients undergoing a gastrectomy.MethodsThirty patients scheduled to undergo a gastrectomy were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…Activation of PAR-2 signal sensitize peripheral nociceptors and leads to a inflammatory pain. UTI is known to inhibit serine proteases, stabilize lysosomal membranes, and inhibit inflammatory cytokine production [7,18]. Thus, it was hypothesized that the inhibition of pro-inflammatory cytokine production by UTI may prevent the initiation of persistent neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of PAR-2 signal sensitize peripheral nociceptors and leads to a inflammatory pain. UTI is known to inhibit serine proteases, stabilize lysosomal membranes, and inhibit inflammatory cytokine production [7,18]. Thus, it was hypothesized that the inhibition of pro-inflammatory cytokine production by UTI may prevent the initiation of persistent neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory mediators such as interleukin-1␤ (IL-1␤), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-␣) are known to play important roles in the progress of pain [3,4]. Inhibition of these cytokines reduces or attenuates nerve injury-induced mechanical allodynia [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Ulinastatin is a serine protease inhibitor which is extensively used clinically in patients with pancreatitis, hemorrhage, shock, or undergoing surgery because of its anti-inflammatory and cytoprotective effects [4,6-8]. Such effects include inhibition of proteases, stabilizing lysosomal membranes, and inhibition of inflammatory cytokine production such as IL-6, IL-8, or TNF-α [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…It has an anti-inflammatory effect through the inhibition of inflammatory factors by suppressing polymorphonuclear leukocyte elastase, TNF-α, and IL-6 [4]. Such anti-inflammatory effect has been known to produce the protection of cells in the case of organ injury [5,6]. Recently, it has been reported that UTI has a neuroprotective effect against cerebral injury [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, in order to confirm this discovery, their research team verified this effect in the septic rat model with recombinant IL-6. However, Park, J. H. et al (Park et al 2010a) found out UTI can reduce the level of stress reaction related cytokine such as IL-6 during gastrointestinal operation, also in the trauma patients with hemorrhagic shock has the similar discovery (Park et al 2010b). This function was also verified by the septic rat model (Cao et al 2010).…”
Section: Inhibit Releasing Of Il-6 To Act As Protective Actionmentioning
confidence: 99%